2021
DOI: 10.1177/01455613211028493
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology-Specific Symptoms May Be Highly Observed in Patients With a History of Covid-19 Infection After Inactivated Coronavirus Vaccination

Abstract: Objective: To evaluate the otolaryngology-specific symptoms that occur after receiving the Covid-19 vaccine and its possible side effects in patients who had Covid-19 infection in the last 6 months before the vaccination. Patients and Methods: The study comprised 3383 health care workers who were vaccinated against Covid 19. After excluding, the study was conducted with 1710 (51%) participants who agreed to answer the study questions. The participants were divided into 2 groups according to the history of Covi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
2
16
0
2
Order By: Relevance
“…For example, the observation by Vaira, L. et al, shows that vaccination does not reduce the incidence of these symptoms [ 32 ]. Avci, H. et al, made similar observations [ 33 ]. These data are inconsistent with our results, which, combined with the small amount of data, indicates the need for further exploration of the topic, especially since these symptoms are one of the most characteristics of COVID-19 [ 6 ].…”
Section: Discussionsupporting
confidence: 54%
“…For example, the observation by Vaira, L. et al, shows that vaccination does not reduce the incidence of these symptoms [ 32 ]. Avci, H. et al, made similar observations [ 33 ]. These data are inconsistent with our results, which, combined with the small amount of data, indicates the need for further exploration of the topic, especially since these symptoms are one of the most characteristics of COVID-19 [ 6 ].…”
Section: Discussionsupporting
confidence: 54%
“…In a large study on 3,383 healthcare workers who received the inactivated COVID-19 vaccine (CoronaVac, Sinovac Life Sciences). Otolaryngology-specific symptoms were showed as significantly more common in subjects with a history of COVID-19 infection ( 16 ). Differently from us, in this case the authors paid attention to the previous infection and postulated that vaccination may play a triggering role in the activation of symptoms in patients with the previous COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since December 2020, as the European Medicines Agency (EMA) approved the first vaccine against COVID-19 (Pfizer-BioNTech), a large immunization campaign commenced and potential vaccine-related adverse effects, including audio-vestibular effects, were reported. Few case reports and small sample studies suggested a possible link between vaccination and an increased risk of SNHL, however with a very low level of evidence [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Even if a clear and defined relationship between the COVID-19 vaccination and SSNH cannot be identified in the literature to date, we expect that further studies and reports on this topic could be available in the future.…”
Section: Discussionmentioning
confidence: 99%